2009
DOI: 10.1007/s12298-009-0041-7
|View full text |Cite
|
Sign up to set email alerts
|

Similarities in the biochemical changes between solar UV exclusion and GA application in Amaranthus caudatus

Abstract: Seedlings of Amaranthus caudatus grown under UV exclusion filters (-UV -B <320nm; -UV -B/A <400nm) in the ambient solar radiation showed an enhancement in growth. This was accompanied by reduction in the synthesis of betacyanin but enhancement in the level of amino acids and proteins. The growth promotion and the accompanying biochemical changes were similar to the external application of GA 3 to the seedlings under ambient solar radiation. The results are discussed in the light of similarities between UV excl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
1
6
0
Order By: Relevance
“…Since secondary and primary metabolic pathways compete for the common pool of carbon, reduction in secondary metabolism can channelize the carbon to primary metabolism. This type of enhanced channelization has been reported with respect to reduced betacyanin synthesis in Amaranthus plants grown under UV excluded sunlight (Sharma and Guruprasad 2009).…”
Section: Discussionsupporting
confidence: 73%
“…Since secondary and primary metabolic pathways compete for the common pool of carbon, reduction in secondary metabolism can channelize the carbon to primary metabolism. This type of enhanced channelization has been reported with respect to reduced betacyanin synthesis in Amaranthus plants grown under UV excluded sunlight (Sharma and Guruprasad 2009).…”
Section: Discussionsupporting
confidence: 73%
“…It was found that elevated amounts of UV‐B radiation may influence physiological and biochemical processes in plant cells, for instance inhibition of photosynthesis, a hindering of nitrogen intake, and, in consequence, an inhibition of cell division, reduction of plant growth and a decrease of plant biomass . The negative influence of UV‐B radiation was confirmed by several UV exclusion studies , . It was shown that the impact of UV‐B irradiation varied considerably for different species and even cultivars, for example the study of two varieties of soybean grown under increased UV‐B radiation showed that yield of one of the cultivars was reduced by about 20%, whereas that of the second one was practically unaffected .…”
Section: Introductionmentioning
confidence: 96%
“…5 The negative influence of UV-B radiation was confirmed by several UV exclusion studies. 1,6 It was shown that the impact of UV-B irradiation varied considerably for different species and even cultivars, for example the study of two varieties of soybean grown under increased UV-B radiation showed that yield of one of the cultivars was reduced by about 20%, whereas that of the second one was practically unaffected. 4 The sensitivity of plants to UV-B depends on air temperature, precipitation and geographic origin of the species; plants growing in areas exposed to high levels of radiation are more tolerant to UV radiation than those which receive moderate irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…Suppression of leaf growth by solar UV and a drastic enhancement in the area of leaves after the exclusion of UV has been observed in plants such as cotton (Dehriya et al 2011) and Amaranthus (Sharma and Guruprasad 2009). The number and the area of rosette leaves were enhanced by the exclusion of UV in WT Arabidopsis also.…”
Section: Discussionmentioning
confidence: 99%